4th National Congress of the Bulgarian Society for Dermatologic Surgery, Sofia, 11th March 2022 with main topics: one step melanoma surgery (OSMS) and drug induced melanoma - Georgi Tchernev; Nikhil Oliveira; Lorraine Joseph Kandathil; James W. Patterson; Jose Carlos Cardoso; Simona Kordeva; Ivan Pidakev; Konstantin Stavrov (PAGEPress Publications, 2022)
Not available